A study on green synthesis, characterization of chromium oxide nanoparticles and their enzyme inhibitory potential - Zainab,; Ahmad, Shujaat; Khan, Idrees; Saeed, Khalid; Ahmad, Hanif; Alam, Aftab; Almehmadi, Mazen; Alsaiari, Ahad Amer; Haitao, Yu; Ahmad, Manzoor (Frontiers in Pharmacology, 2022)
The conventional chemical methods of nanoparticles synthesis have been effectively replaced by nanoparticle synthesis mediated by plants. The current study describes the environmental friendly synthesis of chromium oxide nanoparticles (Cr2O3 NPs) using Erythrophleum guineense plant extract. The synthesis of Cr2O3 NPs was validated by UV/VIS spectroscopy, Energy Dispersive X-Ray (EDX), Scanning Electron Microscopy (SEM), and X-ray diffraction (XRD) studies. The appearance of the Sharpe peak at 460 nm in the UV/Vis spectrum and the colour change caused by surface plasma resonance confirmed the formation of Cr2O3 NPs. The EDX spectrum of Cr2O3 nanoparticles revealed the presence of carbon, oxygen, and chromium, while SEM analysis revealed an irregular round morphology (with a size below 400 nm). In addition, XRD studies suggested their crystalline nature by the characteristic peaks at 34° and 36° and 42° (2Ɵ) respectively. The green synthesized Cr2O3 NPs showed promise as in-vitro cholinesterase inhibitor at tested concentrations (62.5-1000 μg/mL), with IC50 values of 120 and 100 μg/mL against Acetylcholinesterase (AChE) and Butyrylcholinesterase (BChE), respectively. The results suggested that the green synthesized Cr2O3 NPs could be used in the future to stop enzyme from working and for other biological activities.